2009
DOI: 10.1183/09031936.00181808
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin induces pleural and subpleural fibrosis in the presence of carbon particles

Abstract: The pathological changes in idiopathic pulmonary fibrosis (IPF) typically start in subpleural lung regions, a feature that is currently not explained. IPF, as well as bleomycininduced lung fibrosis, are more common in smokers. We hypothesised that carbon particles, which are major components of cigarette smoke that are transported to alveoli and pleural surface, might be involved in the development of subpleural fibrosis through interaction with pleural mesothelial cells.Carbon particles were administered to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 34 publications
7
45
0
Order By: Relevance
“…Wildtype (WT) C57Bl/6j mice and PAI-1 2/2 mice and PAI-1 transgenic (PAI-1 Tg ) mice on a C57Bl/6j background were purchased from Jackson Laboratory (Bar Harbor, Maine). The CBB mouse model of pleural fibrosis was established as previously described in CD1 mice (10), with some modifications. Isofluorane-anesthetized C57BL/6j mice were intrapleurally injected with 100 ml of a CBB mixture (0.1 mg carbon black [Degussa AG, Frankfurt, Germany]/0.07 U bleomycin [Teva Parenteral Medicines, Irvine, CA]) prepared in 0.9% saline.…”
Section: Cbb Mouse Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Wildtype (WT) C57Bl/6j mice and PAI-1 2/2 mice and PAI-1 transgenic (PAI-1 Tg ) mice on a C57Bl/6j background were purchased from Jackson Laboratory (Bar Harbor, Maine). The CBB mouse model of pleural fibrosis was established as previously described in CD1 mice (10), with some modifications. Isofluorane-anesthetized C57BL/6j mice were intrapleurally injected with 100 ml of a CBB mixture (0.1 mg carbon black [Degussa AG, Frankfurt, Germany]/0.07 U bleomycin [Teva Parenteral Medicines, Irvine, CA]) prepared in 0.9% saline.…”
Section: Cbb Mouse Modelmentioning
confidence: 99%
“…Pleural injury is characterized by the proliferation of a-smooth muscle actin (a-SMA)-expressing myofibroblasts (10,11). These cells promote the accumulation of extracellular matrix (ECM) proteins, including collagen (Col)-1 (12).…”
mentioning
confidence: 99%
“…Mesothelial MT (MesoMT) is characterized by mesenchymal changes in cell morphology. Furthermore, increased expression of ␣-SMA and collagen 1 (Col-1) are hallmarks of myofibroblasts (1,2,14,19). Both ␣-SMA and Col-1 were upregulated in mesothelial cells undergoing MesoMT in vivo in a CBB-mediated model of pleural injury in which thrombin and plasmin were upregulated within the injured pleural compartment (19).…”
mentioning
confidence: 99%
“…Our work and that of others has shown that pleural mesothelial cells (PMCs) contribute to the progression of PF by undergoing a process called mesothelial (Meso) mesenchymal transition (MT) (1,2,13,14,19), through which PMCs assume characteristics of myofibroblasts. Mesothelial MT (MesoMT) is characterized by mesenchymal changes in cell morphology.…”
mentioning
confidence: 99%
“…The case against causal association, includes the possibility that PPFE can develop idiopathically or, as some reports suggest, as an abreaction to infectious agents [2], as well as: due to the lack of a clear dose-response curve; development and progression of fibrosis after a free interval of several years after termination of treatment; lack of reversal with drug withdrawal; and absence of robust epidemiological support or absence of a suitable animal model [55]. Current models of pleural fibrosis use transforming growth factor-b1, bleomycin and carbon black instilled in the pleural space as the inciting agents [56,57]. Conversely, in favour of an association between alkylating agents and PPFE are: the normalcy of pre-therapy chest imaging in the study by BEYNAT-MOUTERDE et al [1]; the homogenous and consistent reports of the same distinctive drug-associated disease from different countries over the past 35 years [2]; the notion that two separate alkylating agents can produce an association with PPFE; and the occurrence of PPFE in young individuals [20,25] in whom fibrotic conditions are relatively rare.…”
Section: @Erspublicationsmentioning
confidence: 99%